A Model for the Management Process of Human Resources Recruitment and Selection - Harizanova, Margarita; Lambovska, Maya (Research Papers, 2009)
The determination of human resources as “the most valuable” factor of production is in connected with the competitive power of the organizations. In this sense the competitive power could be achieved by a systematic and purposive selection, use, supporting and development of the human potential. The organizations’ contest for the attracting and the detention of qualified and talented employees requires unavoidably a new, more modern and more pragmatic development of the human resources management science. The efforts of authors of the present study are also along these lines.The study is devoted to the management process of human resources recruitment and selection in the organization. A different model for this process, based on the competent approach, is propounded by authors of the study. The model is submitted by methods for the management process of human resources recruitment and selection and an algorithm for evaluation of candidates for the vacant positions in the organization. The study is worked out in five sections. Subject and aim of the study, tasks and instruments of its authors are clarified in the fist section. A present state analysis of the scientific literature on the problem of human resources recruitment and selection is made in the second section of the study. The main characteristics of the authors’ conception about the management process of human resources recruitment and selection are also brought in the second section. Methods for the management process of human resources recruitment and selection, based on the competent approach and pair-wise comparison method, is presented in the third section of the study. Stages and procedures of the management process are also described in this section. An accent is put on the specificity of the model proposed. According to the authors this specificity first of all finds expression in the use of a non-traditional approach (competent approach) and a non-traditional method for the candidates’ competences evaluation (pair-wise comparison method). The fourth section of the study consists of an algorithm for evaluation of candidates for the vacant positions in the organization. The algorithm is worked out by mixing some nontraditional for the subject of the study instruments (pair-wise comparison method and theory of confidential intervals) and two classical methods (investigation method by questionnaires and Hungarian method for solving the assignment minimization problem). Fifth section of the study covers its conclusion. In the conclusion an accent is put on the theoretical, methodical and practical contributions of the authors of the study.